Pengaruh Biaya Promosi terhadap Volume Penjualan Jahe Ja’M di Kota Samarinda - Hidayah, Nur; AF, Abd. Rachim; Permatasari, Indah (Educational Studies: Conference Series, 2024)
The research in this thesis is motivated by promotion costs which influence sales volume. The aim of this research is to determine the influence and relationship of promotion costs on the sales volume of Ja'M Ginger in Samarinda City. The type of research carried out is quantitative descriptive research. Data collection was carried out by direct observation and data documentation. The data analysis techniques used are simple linear regression test, t test, coefficient of determination test and product moment correlation test. Based on the research results, it shows that promotion costs (X) influence the sales volume (Y) of Ja'M Samarinda Ginger and there is a relationship between promotion costs (X) and sales volume (Y) of Ja'M Samarinda Ginger which, when interpreted on an interpretation scale, includes in the "very strong" category, where the figure lies between 0.80 – 1.00. The influence of the independent variable on the dependent variable is 89.7%. Meanwhile, the remaining 10.3% is influenced by other variables outside the research variables.